2017
DOI: 10.1177/0265407517704091
|View full text |Cite
|
Sign up to set email alerts
|

Infidelity’s aftermath: Appraisals, mental health, and health-compromising behaviors following a partner’s infidelity

Abstract: Guided by transactional stress theory, this research investigated the role of appraisals in noninvolved partners’ mental health and health-compromising behaviors after infidelity. Responses from 232 college students who were recently cheated on revealed that negative appraisals (partner blame, self-blame, and causal attribution) had indirect effects on health-compromising behaviors through mental health (depression, anxiety, and distress). Moderated mediation analyses revealed that gender altered the indirect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 45 publications
2
50
0
4
Order By: Relevance
“…Both decisional and emotional forgiveness are significantly influenced by cognitive appraisals about an event or situation based on personal and environmental coping resources (Strelan, in press). In a marital context, cognitive appraisals which play a major role in how partners respond to interpersonal transgressions can be reflected in attributions of spousal infidelity (Shrout & Weigel, 2018). Attributions are how spousal infidelity is interpreted in terms of causes and accountability (Fincham & Bradbury, 1992;Fincham, Paleari, & Regalia, 2002).…”
mentioning
confidence: 99%
“…Both decisional and emotional forgiveness are significantly influenced by cognitive appraisals about an event or situation based on personal and environmental coping resources (Strelan, in press). In a marital context, cognitive appraisals which play a major role in how partners respond to interpersonal transgressions can be reflected in attributions of spousal infidelity (Shrout & Weigel, 2018). Attributions are how spousal infidelity is interpreted in terms of causes and accountability (Fincham & Bradbury, 1992;Fincham, Paleari, & Regalia, 2002).…”
mentioning
confidence: 99%
“…Partner's infidelity (indicating frustration of relatedness needs) has been linked with psychological symptoms and health compromising behaviors (Shrout & Weigel, 2018). This study also found that "women who reported negative appraisals and high levels of mental health consequences engaged in more health-compromising behaviors".…”
Section: Fulfillment Of Needs Performance Activitiesmentioning
confidence: 51%
“…The experience of extradyadic behaviors without the primary partner's prior consent can be the most painful occurrence for someone who is in an intimate relationship (Luo et al, 2010;Shrout and Weigel, 2018). Specifically, these extradyadic behaviors can have serious consequences, such as low self-esteem, mental problems, loss of trust, decreased personal and sexual confidence, rage, and guilt, and in many cases leads to spousal battering and divorce (Cano and O'Leary, 2000;Shackelford, 2001;Fisher et al, 2008;Russell et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, these extradyadic behaviors can have serious consequences, such as low self-esteem, mental problems, loss of trust, decreased personal and sexual confidence, rage, and guilt, and in many cases leads to spousal battering and divorce (Cano and O'Leary, 2000;Shackelford, 2001;Fisher et al, 2008;Russell et al, 2013). Studies have shown that these negative emotions can be found in both married and unmarried couples experiencing extradyadic behaviors (Mapfumo, 2016;Fincham and May, 2017;Shrout and Weigel, 2018). Extradyadic behaviors also affect other family members, especially children (Wilson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%